A 12-week pilot study of acceptance of a computer-based chronic disease self-monitoring system among patients with type 2 diabetes mellitus and/or hypertension. (September 2019) - Yan, Mian; Or, Calvin
This study tested a structural model examining the effects of perceived usefulness, perceived ease of use, attitude, subjective norm, perceived behavioral control, health consciousness, and application-specific self-efficacy on the acceptance (i.e. behavioral intention and actual usage) of a computer-based chronic disease self-monitoring system among patients with type 2 diabetes mellitus and/or hypertension. The model was tested using partial least squares structural equation modeling, with 119 observations that were obtained by pooling data across three time points over a 12-week period. The results indicate that all of the seven constructs examined had a significant total effect on behavioral intention and explained 74 percent of the variance. Also, application-specific self-efficacy and behavioral intention had a significant total effect on actual usage and explained 17 percent of the variance. This study demonstrates that technology acceptance is determined by patient characteristics, technology attributes, and social influences. Applying the findings may increase the likelihood of acceptance.